Complete guide to mosaic techniques - Fitzgerald, Bonnie (Search Press, 2015)
"The ultimate resource for mosaic techniques and design ideas. Using clear, easy-to-follow step-by-step instructions, mosaic artist Bonnie Fitzgerald guides you though the entire mosaic process from drawing up an idea, cutting and arranging tiles through to grouting, finishing and installing your finished piece." -- Provided by publisher